The role of security measures : Addressing geopolitical risk in Indian hospitality investments - Das, Debojyoti; Dharmani, Pranav; Dutta, Anupam; Basu, Sankarshan (SAGE Publications, 2025)
This study examines the impact of geopolitical risk (GPR) on corporate investments within the Indian hospitality sector. The findings indicate a significant negative relationship between GPR and corporate investment levels. Notably, even financially stable firms cannot completely offset the detrimental effects of GPR. Additionally, investment reductions during periods of heightened GPR are found to be more substantial than the increases observed during periods of reduced GPR. However, the strategic implementation of security measures can substantially mitigate the challenges associated with GPR. These insights offer valuable guidance to regulators and business leaders in emerging markets when making informed investment decisions.
Keywords: corporate investments; hospitality sector; geopolitical risk; terrorist attacks; India; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|